Investigation of Midtrimester Amniotic Fluid Factors as Potential Predictors of Term and Preterm Deliveries (Hindawi Limited, 2006)
<emph>Aims.</emph> Our aim is to investigate, in 13 cases (delivering preterm) and 21 matched (for age, parity, and gestational age) controls (delivering at term), whether midtrimester amniotic fluid concentrations of elastase, secretory leukocyte proteinase inhibitor (SLPI), soluble intercellular adhesion molecule- 1 , and soluble vascular cell adhesion molecule predict asymptomatic intra-amniotic inflammation/infection and preterm labor. <emph> Results.</emph> Concentrations of all substances were not statistically different among mothers, delivering preterm or at term. SLPI concentrations significantly increased in women, going into labor without ruptured membranes, irrespective of pre- or term delivery ( p<.007 , p<.001 , resp) and correlated with elastase ( r=0.508 , p<.002 ). <emph>Conclusions.</emph> Midtrimester amniotic fluid SLPI concentrations significantly decrease when membrane rupture precedes pre- or full-term labor. However, none of the investigated substances predict preterm delivery.